Comparison of the Effects of Compound Training, Plyometric Exercises, and Kettlebell Exercises on Strength, Power, Dynamic Balance, and Pitched Ball Velocity in 30 Male High School Baseball Pitchers Aged 16-19 Years - Kim, JeongHun; Jaber, Hatem; Yim, JongEun (Medical science monitor, 2024)
BACKGROUND The purpose of this study was to determine how the combination of plyometric training (PT), which builds strength through fast, repetitive extensions and contractions, and kettlebell training (KT), using a device that is smaller than a barbell and allows for strength and full-body work, affects the physical performance and performance of high school pitchers during the season. MATERIAL AND METHODS Participants (n=30 males; age group=16-19 years) were randomized into 3 groups: compound training group (CTG) (n=10), plyometric training group (PTG) (n=10), and kettlebell group (KTG) (n=10). All groups performed training twice weekly for 4 weeks. Pre- and post-intervention assessments were conducted on isokinetic strength to measure strength, vertical jump (VJ) to measure power, dynamic balance (Y-balance), and ball speed (BS) to measure baseball performance. RESULTS We found there was increased strength, VJ, Y-balance, and BS in the CTG, PTG, and KTG (p=.000). CTG had significantly different results than PTG and KTG (p=.000). There was a significant difference in increased strength of the right knee joint flexors between PTG and KTG (p=.000). CONCLUSIONS CTG, PTG, and KTG for pitchers during the season improved significantly. These results suggest that combination training, rather than just 1 type of training, affects pitchers' strength, VJ, Y-balance, and BS during the season.